Adverse incorporation and social exclusion in Harare : an analysis of spatial design mobility and accessibility of low-income groups residing in Harare’s southern suburbs - Thebe, Vusilizwe (University of Pretoria, 2025)
Thesis (PhD (Development Studies))--University of Pretoria, 2025.